Computational Interpretations of 2D Muqarnas Projections in 3D Form Finding - Alaçam, Sema; GÜZELCİ, ORKAN ZEYNEL (My University, 2016)
In the scope of this study, we developed an algorithm to generate new 3D geometry (interpretation) of a given or generated planar projection of a muqarnas in a digital 3D modelling software (Rhinoceros), its visual scripting environment (VSE) Grasshopper and also Python programming language. Different than the traditional methods, asymmetrical form alternatives are examined. In other words, 2D projections of muqarnas were only used as an initial geometrical pattern for generative form finding explorations. This study can be considered as an attempt to explore new relations, rules and vocabulary through algorithmic form finding experiments derived from 2D muqarnas projections.
Keywords: muqarnas; form finding